PROCESS AND STRATEGY ANALYSIS IN LEARNING TO DRAW MOUNTAINS IN THE SBDP SUBJECT FOR GRADE 4 AT SD 2 KARANGMALANG - Janita Putri Dwihana; Wasis Wijayanto (Eduarts: Jurnal Pendidikan Seni, 2025)
Art education in elementary schools, particularly drawing mountains in the Arts, Culture, and Crafts (SBDP) subject, serves as a means to develop students' creativity, motor skills, and self-expression. This study aims to analyze the process of students drawing mountains and the learning strategies of teachers in grade 4 at SD Negeri 2 Karangmalang, with a focus on enhancing creativity through a holistic approach. Using a qualitative descriptive method, data were collected through observation, interviews, and documentation from teachers and students. The results show that the students' process includes the stages of observing objects, creative imagination, and applying elements of fine arts such as lines, planes, shapes, and rhythmic patterns, supported by fine motor skills. Meanwhile, the teachers' strategies included object introduction, step-by-step modeling, exploration media, and reflective evaluation, which were effective in building confidence and producing realistic and aesthetic drawings. The conclusion of the study confirmed that this approach not only enhanced students' creativity but also supported holistic development, with recommendations for the integration of technology in art education to enrich future experiences.